Impact of six consecutive days of sprint training in hypoxia on performance in competitive sprint runners - Kasai, N.; Mizuno, S.; Ishimoto, S.; Sakamoto, E.; Maruta, M.; Kurihara, T.; Kurosawa, Y.; Goto, K. (The Journal of Strength and Conditioning Research, 2019)
The purpose of this study was to determine the effects of 6 successive days of repeated sprint (RS) training in moderate hypoxia on anaerobic capacity in 100-200-m sprint runners. Eighteen male sprint runners (age, 20.0 ± 0.3 years; height, 175.9 ± 1.1 cm; and body mass, 65.0 ± 1.2 kg) performed repeated cycling sprints for 6 consecutive days in either normoxic (NOR; fraction of inspired oxygen [FiO2], 20.9%; n = 9) or hypoxic conditions (HYPO; FiO2, 14.5%; n = 9). The RS ability (10 × 6-second sprints), 30-second maximal sprint ability, maximal oxygen uptake (VO2max), and 60-m running time on the track were measured before and after the training period. Intramuscular phosphocreatine (PCr) content (quadriceps femoris muscle) was measured by 31P-magnetic resonance spectroscopy (31P-MRS) before and after the training period. Both groups showed similar improvements in RS ability after the training period (p < 0.05). Power output during the 30-second maximal sprint test and VO2max did not change significantly after the training period in either group. Running time for 0-10 m improved significantly after the training period in the HYPO only (before, 1.39 ± 0.01 seconds; after, 1.34 ± 0.02 seconds, p < 0.05). The HYPO also showed a significant increase in intramuscular PCr content after the training period (before, 31.5 ± 1.3 mM; after, 38.2 ± 2.8 mM, p < 0.05). These results suggest that sprint training for 6 consecutive days in hypoxia or normoxia improved RS ability in competitive sprint runners.